DIRECT AND INDIRECT EFFECTS OF WORK EXPERIENCE, COMPETENCE ON SATISFACTION AND PERFORMANCE ASN AT THE WOMEN'S EMPOWERMENT AND CHILD PROTECTION SERVICE OF EAST KUTAI REGENCY - Meita Sondang Riski; Endang Prihatiningsih; Siti Aisyah; Jumri (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
The purpose of this study is to analyze the performance of ASN at the Women's Empowerment and Child Protection Service of East Kutai Regency. The analytical method used is Path Analysis where the data is processed using the SPSS (Statistical Program For Social Science) version 23 computer programming application. From the results of the analysis of work experience and competency variables on ASN satisfaction, the correlation value of R is 0.831 and the coefficient of determination R2 is 0.691, providing an illustration that the relationship between work experience (X1) and competency (X2) variables together on ASN satisfaction (Y1) is classified as very strong. Based on the regression coefficient value of each variable, the functional relationship between the independent variables and the dependent variable (satisfaction) can be formulated in the following regression equation: Y1= 4.056 - 0.199 X1+ 0.737 X2. Meanwhile, the results of the analysis of work experience and competency variables on ASN performance, the correlation value of R is 0.578 and the coefficient of determination R2 is 0.334, which illustrates that the relationship between work experience variables (X1) and competency (X2) together on ASN performance (Y2) is classified as moderate. Based on the regression coefficient value of each variable, the functional relationship between the independent variable and the dependent variable (performance) can be formulated in the following regression equation: Y2 = 11.929 - 0.358 X1+ 0.654 X2. The conclusion of this study is that the influence of work experience variables on ASN satisfaction or performance is not significant, competency variables on satisfaction or performance are significant, the influence of satisfaction on ASN performance is significant and the indirect influence of work experience or competency variables is not significant.